KELAYAKAN EKONOMI JALAN BATAS KOTA TAPAKTUAN – BAKONGAN DITINJAU DARI SEGI CONSUMER SURPLUS - Khuzaifah Khuzaifah; Sofyan M. Saleh; Renni Anggraini (JURNAL TEKNIK SIPIL, 2017)
Abstract: Roads border of Tapaktuan-Bakongan municipality in the province of Aceh  is the only road to North Sumatra Province on the South Western main line. This road is in the mountainous area of the existing road with a width of only 3.5-4.5 meters tall, narrow and winding up with a small radius. Road construction along the 3.5 km. on site km. s/d 460+200 km. 463+700 with the most critical segment of the road is handled by construction Cantilever on 460+900 KM up to 462+650 KM along the 1.75 km. The purpose of this research was to examine the feasibility of economic development path with the method of Consumer Surplus, and cost-saving benefits of Operational Vehicles Cost (VOC), with the Pacific Consultant International (PCI) method, and time value uses productivity method.  Analysis of economic feasibility of the Bina Marga is done by means of Benefit Cost Ratio (BCR), Net. Present Value (NPV), Economic Internal Rate of Return (EIRR) and Sensitivity Analysis. The results of research on prediction of traffic flow with the growth rate of the average vehicle is 1.49%. per year. The benefits gained in terms of consumer surplus toward the construction of the new roads are in a form of the savings of VOC, passenger cars is Rp870/veh/km, bus is Rp1.149/veh/km and trucks is Rp2,749/veh/km. Savings time value obtained on new roads, vehicle passenger car Rp11,016/kend, vehicle bus, Rp73,439/kend, vehicle truck Rp7,344/veh. An analysis of the Economic Feasibility of the 25th year since the road opened the economic feasibility of the standards for all the discount rates. At a discount rate of 10%, BCR value is 1.93, NPV value is Rp75,172,122,823.- on the discount rate of 12% the value of BCR is 1.51, the value NPV is Rp39,298,870,060.- and at a discount rate of 15% of the value, the BCR value is 1.09, the value of NPV is Rp 6,540,471,105.-. and with the value of the EIRR obtained at discount rate 15.89%, this indicates that the construction of roads of Tapaktuan – Bakongan is feasible to be implemented.Abstrak: Ruas jalan Batas Kota Tapaktuan-Bakongan yang terletak di Provinsi Aceh merupakan satu-satunya jalan menuju Provinsi Sumatera Utara pada lintas Barat Selatan. Ruas jalan ini berada pada daerah pegunungan dengan lebar badan jalan eksisting hanya 3,5-4,5 meter, sempit dan berliku dengan radius kecil. Pembangunan jalan sepanjang 3,5 km. di lokasi KM. 460+200 s/d KM. 463+700 dengan segmen yang paling kritis dari ruas jalan tersebut ditangani dengan konstruksi Cantilever pada KM 460+900 sampai dengan KM 462+650 sepanjang 1,75 km. Tujuan dari penelitian ini untuk mengkaji kelayakan ekonomi pembangunan jalan dengan metoda Consumer Surplus, manfaat penghematan Biaya Operasional Kendaraan (BOK), dengan metode Pacific Consultant International (PCI), dan Nilai Waktu menggunakan metode Produktifitas. Analisis kelayakan ekonomi dengan menggunakan metode Bina Marga berdasarkan Benefit Cost Ratio (BCR), Net Present Value (NPV), Economic Internal Rate of Return (EIRR) dan Analisis Sensitivitas. Hasil penelitian terhadap prediksi arus lalu lintas dengan tingkat pertumbuhan kendaraan rata-rata adalah 1,49%. per tahun. Manfaat yang diperoleh dari segi consumer surplus terhadap jalan baru berupa penghematan BOK, mobil penumpang sebesar  Rp 870 /kend/km, kenderaan bus sebesar Rp. 1.149 /kend/km dan truk sebesar Rp. 2.749 /kend/km. Penghematan nilai waktu yang diperoleh pada jalan baru, kendaraan mobil penumpang Rp. 11.016 /kend, kendaraan bus, Rp. 73.439 /kend, kendaraan truk Rp.7.344 /kend. Analisis terhadap Kelayakan Ekonomi tahun ke 25 sejak jalan dibuka memenuhi standar kelayakan ekonomi untuk semua discount rate. Pada discount rate 10% nilai BCR 1,93 nilai NPV Rp. 75.172.122.823,- pada discount rate 12% nilai BCR 1,51 nilai NPV Rp. 39.298.870.060,- dan pada discount rate 15% nilai BCR 1,09 nilai NPV Rp. 6.540471.105,-. dan dengan Nilai EIRR diperoleh pada discount rate 15,89%, ini menunjukkan bahwa pembangunan jalan Batas Kota Tapaktuan–Bakongan layak  untuk dilaksanakan.